CHAPTER 3 SURFACE AND INTERFACE CHEMISTRY OF CLAY MINERALS - Schoonheydt R.A.; Johnston C.T. (My University, 2006)
This chapter on surface and interface chemistry of clay minerals follows a bottom-up approach. It starts with the properties of surface oxygens and hydrogens as influenced by chemical composition and structure. Then, three types of surfaces are described: surfaces with a permanent charge, neutral siloxane surfaces and hydroxyl surfaces. The remaining part of the chapter is devoted to a discussion of the interaction of these surfaces with water, dye molecules, and transition metal ion complexes with emphasis on chiral clay minerals and proteins. The chapter ends with the synthesis of hybrid films, consisting of alternating layers of clay minerals and cationic polyelectrolytes, amphiphilic alkylammonium cations, amphiphilic cationic dyes, or cationic proteins. These films are discussed in the light of the preparation of advanced functional materials.